As representações das identidades femininas na série mulheres espetaculares do programa esporte espetacular - Santos, Barbara Tatiane de Avila (2018)
This study proposes to analyze images of feminine identity revelation of structures television series "Spectacular Women" in the program Spectacular Sports TV Globo. The study aims to understand which representations of the woman's identities that the series presents and/or privileges and/or excludes, through the identification of cultural elements and the ways in which the presented identities and cultures are used and identify the elements that define " Spectacular Women". The work is based on a cultural analysis of the media with the methodological contribution of cultural based on the Williams (1979, 2003) Sentiment Structures and hegemony, combined with the textual analysis of Casetti and Chio (1999). As a result of this impressive women are defined by sharing independence, determination and humanity. It was also verified the rich diversity of representations of feminine identities, with different ages, ethnicities, social classes, race, physical forms, cultures, and religions. However, there are other women's identities, particularly in relation to social roles, suppression, e.g., Mother, sisters, grandparents, physiotherapists, teachers, and trainers. Nevertheless, the series is somewhat audacious in bringing counter-hegemonic forces, o it collaborates to guarantee the ideals and interests that fight gender-based differences in society, although there is still a lack of problematization of the identities represented there.